Penguatan Kapasitas Budidaya dan Pascapanen untuk Peningkatan Daya Saing Melon Hidroponik KT Suryo Farm - Arif Umami; Ni Kadek Ema Sustia Dewi; Herdiana Anggrasari (Dharma: Jurnal Pengabdian Masyarakat, 2026)
The Suryo Farmers Group (KT) in Mantrijeron, Yogyakarta City, is a productive community of 26 members. Founded in 2022, the group has demonstrated a strong commitment to utilizing limited land for crops such as mint, lettuce, and cucumbers, and even serves as an agricultural education center. However, its farming development efforts were inhibited by significant failures in hydroponic melon cultivation, with 95% of the crops failing due to disease. Factors contributing to this failure included a damaged greenhouse and members' lack of knowledge regarding cultivation practices, pest and disease management, post-harvest management, and marketing. To address these issues, an integrated community service program was implemented, combining intensive mentoring with knowledge enhancement through a series of outreach and training sessions. The intervention focused on four crucial aspects: proper hydroponic melon cultivation techniques, pest and disease management (PDM), post-harvest handling, and marketing management. The program's effectiveness was measured by comparing quantitative pre-test and post-test results, with a target of a minimum 70% increase in knowledge. The implementation of this activity, involving 26 members, demonstrated significant knowledge gains across all aspects. Data shows a sequential increase in knowledge for Cultivation (from ≈67% to ≈78%), PDM (from ≈63% to ≈85%), Post-Harvest (from ≈83% to ≈93%), and Marketing (from ≈88% to ≈98%). The highest increase occurred in the Marketing and PDM aspects, which directly address the group's main obstacles. The success of this program is expected to be the foundation for KT Suryo Farm to carry out sustainable melon cultivation, produce high-quality products, and implement strong marketing strategies, thereby being able to stabilize and increase the group's turnover.